MECHANICAL PROPERTIES OF DRAMIX HOOKED END STEEL FIBER REINFORCED CONCRETE - Falmata A. Mustapha (International Journal of Innovations in Engineering Research and Technology, 2023)
Concrete and other cementitious materials are renowned for their poor tensile strength and brittle failure. One of the best ways to combat the brittleness of cementitious materials is by using steel fibres. This research aims to provide knowledge on the properties of steel fibre-reinforced concrete. The research will focus mainly on the mechanical properties of concrete reinforced with Dramix hooked-end steel fibre with different proportions of 0%, 0.5%, 1%, 1.5%, and 2%. The evaluation of concrete properties will include the workability of concrete using a slump test, compressive strength test, splitting tensile test, and flexural strength test at the age of 7 and 28 days of curing. The slump values of steel fibre reinforced concrete (SFRC) are lower to the tune of 1.74 – 6.97 %. There is an increase in compressive strength of SFRC from 4.37% - 15.11%. The maximum increase in splitting tensile strength of 15% was obtained at a steel fibre volume fraction of 2.0%. The addition of steel fibres significantly improves the mechanical properties of concrete. A 2% volume of steel fibre is recommended as the optimum steel fibre context in concrete for practical applications.